ATR-FTIR-based fingerprinting of some Cucurbitaceae extracts: a preliminary study - Wirginia Kukula-Koch (Acta Societatis Botanicorum Poloniae, 2018)
The attenuated total reflectance-Fourier transform infrared (ATR-FTIR) fingerprinting of some selected cucurbits was performed on three types of seed extracts (alcoholic, cold-water, and hot-water) in order to elaborate a characteristic FTIR profile of their family representatives and to determine their biochemical content. Cluster analysis and principal component analysis were performed on Cucumis melo subsp. melo var. inodorus, Cucurbita pepo, C. maxima, C. pepo var. cylindrica, C. maxima subsp. maxima convar. maxima ‘Hokkaido’ to determine the similarities between their seed extracts. The ethanol extract of the C. pepo seeds was different from the other seed extracts because in addition to esters, it contained free fatty acids, which could influence its pharmacological activity. The main variable differentiating the extracts was the absorption band at 2,920–2,925 cm−1, which represented saturated fatty acids. The obtained results were analyzed by various statistical tools to evaluate the fingerprints of the selected species of cucurbits.